2015
DOI: 10.1021/bk-2015-1210.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Associated with Using Retorts To Limit Mercury Exposure in Artisanal and Small-Scale Gold Mining: Case Studies from Mozambique, Ecuador, and Guyana

Abstract: Artisanal and small-scale gold mining (ASGM) is recognized as the number one source of anthropogenic mercury pollution in the world. Miners use mercury to amalgamate gold, then heat the amalgam to evaporate the mercury. This process, referred to by miners as burning, releases large quantities of mercury vapor that affects the health of miners and community members. A retort is a mercury capture device that provides a simple solution to reduce human exposure to mercury vapor during the burning process. In spite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Mercury is a significant source of concern due to the spread of the activity across the interior of the country and the dependence of many of the indigenous communities that live in and around mining areas on fish as a key source of protein (Watson et al, 2020). The issue has been examined by a growing range of literature (Vieira, 2006;Hilson & Vieira, 2007;Howard et al, 2011;Kiefer et al, 2015).…”
Section: Guyana Mining Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury is a significant source of concern due to the spread of the activity across the interior of the country and the dependence of many of the indigenous communities that live in and around mining areas on fish as a key source of protein (Watson et al, 2020). The issue has been examined by a growing range of literature (Vieira, 2006;Hilson & Vieira, 2007;Howard et al, 2011;Kiefer et al, 2015).…”
Section: Guyana Mining Backgroundmentioning
confidence: 99%
“…The most well documented impact of the ASM sector in Guyana is the mercury discharge issue. In the Guyanese context, a number of studies have examined the mercury problem in more depth (Miller et al, 2003;Hilson & Vieira, 2007;Howard et al, 2011;Kiefer et al, 2015;Watson et al, 2020). The United Nations estimates that the ASM sector in Guyana imports between 7.5 -22.5 tonnes of mercury annually (Legg, Ouboter and Wright, 2015) costing between US$240,000 -US$720,000 annually.…”
Section: Ecological Dimensionmentioning
confidence: 99%
“…The Lumex is prone to memory effects at high concentrations of Hg 0 . In addition, previous studies have demonstrated that the Lumex can itself become contaminated in communities where the burning of amalgams occurs, requiring repair and recalibration by the manufacturer [20] . To this end, a Mercury Instruments Mercury Tracker 3000 IP (MTIP) Hg 0 vapor analyzer is used to measure Hg 0 vapor concentrations in advance of the Lumex.…”
Section: Data Collection In the Fieldmentioning
confidence: 99%
“…Interestingly, there seems to be a reluctance among ASGMs to employ the use of a retort which could provide a medium to reduce exposure to vaporous mercury. Even though it is less expensive, easy to use, and globally recommended, non-compliances have been reported in Ghana (3), Mozambique, Ecuador, and Guyana (50).…”
Section: Specific Occupational Activity and Ppe Non-compliance Among mentioning
confidence: 99%